2012
DOI: 10.1016/j.ultsonch.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical growth of antimony selenoiodide in multiwalled carbon nanotube

Abstract: This paper presents, for the first time, the nanocrystalline, semiconducting antimony selenoiodide (SbSeI) grown in multi-walled carbon nanotubes (CNTs). It was prepared sonochemically using elemental Sb, Se, and I in the presence of ethanol under ultrasonic irradiation (35 kHz, 2.6 W/cm2) at 323 K for 3 h. The CNTs filled with SbSeI were characterized by using techniques such as powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, high-resolution transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The results that were obtained showed that in this variety of Hordeum, AuNPs regardless of their size (5 nm and 20 nm) and concentration (10 µm/ml and 50 µm/ml) or the length of the treatment (several hours and a few days) did not enter the roots in the hydroponic culture. The High-Resolution Transmission Electron Microscopy (HRTEM) technique 23 was used to determine the physical nature of the electron-dense dots within the samples, which enabled the precise distinction between the AuNPs and the other electron-dense dots that were present in the electronograms of the root cells. Analyses were performed to verify the presence of AuNPs in the cell compartments, both in the symplast and the apoplast.…”
Section: Introductionmentioning
confidence: 99%
“…The results that were obtained showed that in this variety of Hordeum, AuNPs regardless of their size (5 nm and 20 nm) and concentration (10 µm/ml and 50 µm/ml) or the length of the treatment (several hours and a few days) did not enter the roots in the hydroponic culture. The High-Resolution Transmission Electron Microscopy (HRTEM) technique 23 was used to determine the physical nature of the electron-dense dots within the samples, which enabled the precise distinction between the AuNPs and the other electron-dense dots that were present in the electronograms of the root cells. Analyses were performed to verify the presence of AuNPs in the cell compartments, both in the symplast and the apoplast.…”
Section: Introductionmentioning
confidence: 99%
“…This review summarizes results of recent investigations [11][12][13][14] of carbon nanotubes (CNTs) filled with ternary chalcohalides formed from the group 15-16-17 elements, i.e. antimony sulfoiodide (SbSI) and antimony selenoiodide (SbSeI) known as SbSI-type materials.…”
Section: Nanowires -Recent Advancesmentioning
confidence: 99%
“…Both SbSI and SbSeI were prepared in CNTs ultrasonically from the constituents (the elements Sb, I, and S or Se) [11][12][13][14]. Methanol and ethanol served as the solvents for these reactions, respectively.…”
Section: Preparation Of Sbsi@cnts and Sbsei@cntsmentioning
confidence: 99%
See 2 more Smart Citations